THE ROLE OF GOLD AS SAVE HAVEN OR DIVERSIFIER INVESMENT IN INDONESIA - Sri Nawatmi; Agus Budi Santosa; Agung Nusantara (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
This research is based on the phenomenon of increasing gold transactions in the early 2020 pandemic as an alternative investment. This study aims to answer whether gold acts more as an alternative investment tool or as a diversifier, or is it still relevant as a hedging tool or a safe haven. This study will explore a number of main variables, namely: gold prices, investment interest rates, liquid stock prices, exchange rates and consumer price levels. The data analysis is time-series data with a time span of January 2018 to October 2020. The analytical method used is pairwise correlation and cross-correlation. The results showed, through pairwise correlation analysis, it can be concluded that the gold price variable is more worthy of being called a good store of value or safe haven than its role as an alternative investment or diversification. On the other hand, based on a cross-correlation analysis involving time-lag, the gold price expectation variable for next year has a strong complementarity with the expected investment interest rate variable as well as the expected exchange rate variable. Meanwhile, the relationship between the expected gold price variable and the expected liquid stock price variable, which is often used as an investment tool indicator, has a very strong substitution or diversification relationship.